The Al Umanaa Foundation's Literacy Strategies at SMP and SMA Al Umanaa Boarding School, Sukabumi - Supriatnoko; Hastuti Redyanita; Ida Bagus Putu Suamba (Soshum: Jurnal Sosial dan Humaniora, 2024)
The research addresses the challenges, objectives, methods, results, and conclusions of cultivating literacy programs at SMP and SMA Al Umanaa Boarding Schools. The main issue identified is the limited student engagement in the School Literacy Movement (SLM) due to time constraints and lack of motivation, while the objective is to investigate the strategies employed by the Al Umanaa Foundation to cultivate a literacy culture. Using a qualitative method, data were collected through interviews, observations, and documentation studies, focusing on participants such as school principals, literacy teams, teachers, and library managers. The study reveals that the Al Umanaa Foundation effectively adapts the literacy learning syllabus to the national curriculum, creates a conducive physical environment, and involves the community in literacy activities. Key initiatives include providing reading corners, literacy corners, and libraries, as well as engaging students in competitions and training programs. Despite encountering financial constraints and limited government support, the foundation has successfully utilized community collaborations and innovative funding strategies to sustain its literacy programs. The research concludes that a comprehensive and collaborative approach, integrating physical, social, and academic environments, is essential for cultivating a robust literacy culture. The Al Umanaa Foundation's strategies can serve as a model for other educational institutions aiming to enhance literacy and academic performance.